A new fluorescence chemosensor for selective detection of copper ion in aqueous solution. Issue 21 (25th May 2016) - Hu, Yang; Ke, Qian; Yan, Chang; Xu, Cai-Hua; Huang, Xiao-Huan; Hu, Sheng-li
Graphical abstract: Sensor1 for selective detection of Cu 2+ with fluorescence quenching. Highlights: A new fluorescent chemosensor1 based upon 2, 5-diphenylfuran and di(2-picolyl)amine (DPA) was synthesized. The structure of the sensor1 was confirmed by single crystal X-ray diffraction. The sensor1 can be used to determine Cu 2+ in aqueous DMSO with high selectivity. Abstract: A new fluorescent chemosensor based upon 2, 5-diphenylfuran and di(2-picolyl)amine (DPA) was designed and synthesized. Its structure was confirmed by single crystal X-ray diffraction and its photophysical properties were studied by absorption and fluorescence spectra. This compound can be used to determine Cu 2+ ion with high selectivity among a series of cations in aqueous DMSO. This sensor forms a 1:1 complex with Cu 2+ and displays fluorescent quenching.